ANALISIS KETEPATAN AKURASI PASSING KAKI BAGIAN DALAM SEPAK BOLA PADA SISWA SEKOLAH SEPAK BOLA (SSB) INDONESIA MUDA KECAMATAN SELUMA UTARA KOTA BENGKULU - Putra, Sandi; Juwita, Juwita; Anggara, Deffri (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the accuracy analysis of inside leg passing accuracy for Indonesia Muda Football School (SSB) students. This research is a qualitative descriptive research. The population in this study was 20 students at the Indonesia Muda Football School (SSB), North Seluma. The test instrument used is the inside leg passing test using a cone.The results of this research test show that the accuracy of passing the inside foot of football for students at the Indonesia Muda Seluma Utara Football School (SSB) in 2023 is in the very good category, 5% (1 student). with good category, 30% (6 students). with the medium category, 45% (9 students). less category, 15% (3 students). And the very poor category, 5% (1 student).